Equivalence testing with particle size distribution data: methods and applications in the development of inhalative drugs - Hoffelder, Thomas; Wellek, Stefan (Statistics in biopharmaceutical research, 2017)
Key criteria of the quality of inhalative drugs are assessed in experiments generating so-called particle size distributions as data. Many experiments of that kind are carried out to demonstrate that necessary modifications to whatever part of the manufacturing process do not substantially change basic characteristics of an inhalable drug product. The equivalence testing procedures we derive for that purpose rely on different models accommodating the specific structure of such data and on different ways of specifying the region of nonrelevant differences. For each hypotheses formulation, three different tests are derived (two parametric and one asymptotically distribution-free procedures) and compared in terms of level and power. The results support the conclusion that the asymptotically distribution-free procedure exhibits surprisingly favorable properties. Supplementary materials for this article are available online.
Gesehen am 05.04.2018